Analisis Strata Norma Roman Ingarden dalam Puisi “Doa Seorang Pesolek” Karya Joko Pinurbo - Dania Kusuma Wardani; Wawan Hermawan; Taufiq Hidayat; Salsa Devista Mayangsari; Misbahul Khanif (STIKes Ibnu Sina Ajibarang, 2025)
This research is a qualitative descriptive study with the aim of analyzing the use of Roman Ingarden norm strata in the poem